CETA without Blinders: How Cutting "Trade Costs and More" Will Cause Unemployment, Inequality, and Welfare Losses. Issue 4 (1st October 2016) - Kohler, Pierre; Storm, Servaas
Abstract: Proponents of the Comprehensive Economic and Trade Agreement (CETA) emphasize its prospective economic benefits, with economic growth increasing due to rising trade volumes and investment. Widely cited official projections suggest modest GDP gains after about a decade, varying from between 0.003% and 0.08% in the European Union and between 0.03% and 0.76% in Canada. However, all these quantitative projections stem from the same trade model, which assumes full employment and neutral (if not constant) income distribution in all countries, excluding from the outset any of the major risks of deeper liberalization. This lack of intellectual diversity and of realism shrouding the debate around CETA's alleged economic benefits calls for an alternative assessment grounded in more realistic modeling premises. In this paper, we provide alternative projections of CETA's economic effects using the United Nations Global Policy Model (GPM). Allowing for changes in employment and income distribution, we obtain very different results. In contrast to positive outcomes projected with full-employment models, we find CETA will lead to intra-EU trade diversion. More importantly, in the current context of tepid economic growth, competitive pressures induced by CETA will cause unemployment, inequality, and welfare losses. At a minimum, this shows that official studies do not offer a solid basis for an informed decision on CETA.